Limitations of electrocardiographic criteria of left ventricular hypertrophy in differentiation between hypertrophic cardiomyopathy, cardiac amyloidosis and Fabry disease - Mateusz Tometczak; Judyta Znamirowska; Justyna Topa; Patrycja Pastor; Damian Waksmundzki; Adam Grzebinoga; Katarzyna Mizia-Stec (Śląski Uniwersytet Medyczny w Katowicach, 2024)
Introduction: Left ventricular hypertrophy (LVH) is a common pathology and should be differentiated using non-invasive and invasive methods. Electrocardiography (ECG) is the first choice method for the clinical evaluation of patients with LVH. Material and methods: A retrospective analysis of 77 patients (pts; age: 54.1 ± 16.3; 50.6% men) with features of cardiac hypertrophy in an echocardiographic examination was performed. The population was divided into three subgroups: 60 pts with hypertrophic cardiomyopathy (HCM), 11 pts with cardiac amyloidosis (CA) and 6 pts with Fabry disease (FD). Multiple ECG records were evaluated and the presence and frequency of eight different LVH criteria were verified. Results: Among the study population LVH criteria were present in 67.6% pts with HCM, 53.8% pts with CA and 57.1% pts with FD. Analysis of the number of LVH ECG criteria revealed: none of LVH ECG criteria: in 32.4% pts of HCM, in 46.2% pts with CA, in 42.9% pts with FD; 1 LVH ECG criterion in 21.1% pts with HCM, 46.2% pts with CA and 14.3% pts with FD; 2-4 criteria in 33.8% pts with HCM, 7.7% pts with CA and 42.9% pts with FD; 5-7 criteria in 12.7% pts with HCM and no pts with CA or FD. No patient fulfilled the eight LVH ECG criteria. Conclusions: Electrocardiographic LVH criteria are not sensitive indicators of LVH. The mismatch between transthoracic echocardiography (TTE) and ECG findings is characteristic for CA and FD that may raise the suspicion of these diseases. The lack of LVH ECG criteria do not exclude these diagnoses.